Speaking Performance and Obstacles Encountered by University-Level English Major Students - Engelina Salainti; Alfrits Roul Sinadia (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the speaking difficulties experienced by English major students, addressing the limited qualitative insights into how these learners perceive and manage such challenges in real communicative contexts. Employing a qualitative case study approach, data were collected from four university students through semi-structured interviews, recorded as mobile voice notes and transcribed verbatim to ensure accuracy. The findings reveal that linguistic obstacles, particularly difficulties in vocabulary retrieval and grammatical construction, contribute to frequent use of fillers such as “ee” and “hmmm,” indicating processing challenges during speech production. In addition, psychological factors, especially anxiety and fear of negative evaluation, significantly hinder students’ speaking performance by increasing their affective filter. Environmental factors, including an overemphasis on theoretical instruction, further limit opportunities for meaningful speaking practice. Despite these challenges, students demonstrate strategic competence by employing paraphrasing, simple expressions, and non-verbal cues to maintain communication. These findings suggest that effective language instruction should balance linguistic development with psychological support and provide more opportunities for communicative practice in supportive learning environments.